Atlas.ti as a tool for analysis of qualitative research according phenomenological approach - Kluber, Tiago Emanuel (Universidade Estadual de Campinas, 2014)
There's, in the context of research in the humanities and social sciences, an emerging discussion about the use of new technologies in analytical processes, therefore, what concerns to the use of qualitative or quantitative data analysis software. In this perspective, this paper, we present the potential of using Atlas.t.i software, guided by way of thinking the qualitative research according to a phenomenological approach. The question we set up is the following: how to show the potential of the Atlas ti software when used as an analytical tool in the phenomenological approach research? As long as the question we discus about phenomenology, the software, and about the potential and cautions arising from its use in this research approach.